Effects of ceria/zirconia ratio on properties of mixed CeO_2-ZrO_2-Al_2O_3 compound - 李红梅 祝清超 李移乐 龚茂初 陈永东 王健礼 陈耀强 (Journal of rare earths, 2010)
A series of CexZr0.50-xAl0.50O1.75(0.05≤x≤0.45) mixed oxides with different Ce/Zr ratio were prepared by co-precipitation method and characterized by means of X-ray diffraction(XRD),Brunauer-Emmet Teller method(BET),temperature-programmed reduction(H2-TPR) and oxygen pulsing technique.The XRD results showed that all samples kept the single CeO2 cubic fluorite structure after calcination at 600 and 1000 oC for 5 h.The results of BET revealed that CexZr0.50-xAl0.50O1.75 with Ce/Zr molar ratio 1/1 exhibited hi...